Analysis of antigens of Philippine fasciola gigantica cobbold, 1885 towards the development of a monoclonal antibody-based antigen capture assay - Padilla, Mildred A. (2000)
This dissertation aims to develop and evaluate a sandwich ELISA to detect antigen in serum of naturally infected carabaos (Bubalus bubalis). Excretory-secretory products were recovered from Philippine Fasciola gigantica adult (FgES) and juvenile (FgJES) worms cultured in vitro. By SDS-PAGE analysis, FgES and FgJES shared molecules with molecular mass of 12-14, 15, 17, 26, 30, 43 and 63 kDa. FgES was chosen over FgJES as the source of diagnostic antigen because the adult worms were abundant compared to the juveniles. Moreover, the use of adult ES products was justified based on the demonstration of shared molecules by SDS-PAGE analysis and the finding of a 12-14 kDa antigen that was shown in several studies to be present in early Fasciola infection. By immunoblotting and indirect ELISA, cross reactivity was observed among F. gigantica, Schistosoma japonicum and Fischoederius spp. Eleven molecules in FgES were recognized by sera from rabbits immunized with FgES. These were in the approximate moleculas maa of 12-14, 17, 23, 25, 26, 28, 33, 36, 38, 45 and 55 kDa. All except the 38 kDa molecule were also recognized by sera from rabbits immunized against the adult worm antigen of S. japonicum. Sera from rabbits immunized against somatic extracts of Fischoederius spp. recognized ES antigens in the estimated molecular mass of 15, 23 and 33 kDa. The cross reactions observed when assaying for Fasciola antibodies point to the need for a specific immunodiagnostic test which discriminates an infection due to Fasciola from other parasites since multiple helminth infection is the rule rather than the exception. FgES was used to immunize BALB/c mice to produce monoclonal antibodies specific for FgES. Five MAbs were generated of IgM and IgG1 isotypes, kappa chain and all recognized the 12-14 kDa molecule in FgES. Compared to others, the target epitope recognized by MAb1H3F7 was species-specific, showing no cross reactions with Schistosoma japonicum or Fischoederius spp. The target epitopes of the remaining MAbs namely, 2C10E3, 1H3F7, 1H8C11 and 2D11B4 cross reacted.